(untitled) (The International Journal for Scientific Research, 2026)
This research examines the concept of pledge (mortgage/security interest) as one of the most important legal guarantees for obligations. It aims to clarify the legal definition of pledge, analyze its legal nature, and distinguish between its principal forms, namely movable pledge and real estate mortgage. The significance of this topic lies in the essential role of pledge in protecting creditors’ rights and strengthening confidence in financial and commercial transactions by allocating specific property as security for the performance of a debt. The study adopts a descriptive and analytical methodology through the examination and interpretation of relevant legal provisions, with particular reliance on the Saudi Commercial Pledge Law as the primary legislative framework governing pledges over movable property. The analysis demonstrates that a pledge constitutes an accessory real right that is dependent upon the secured obligation. It grants the creditor two fundamental rights: the right of priority over other creditors and the right to trace and enforce against the pledged asset in the event of non-payment. The research further explains that pledges are classified according to the nature of the secured asset into movable pledges and real estate mortgages. Although both types share the same objective of securing the creditor’s claim, they differ in terms of legal requirements, registration procedures, and enforcement mechanisms. The study also highlights the modern legislative approach adopted by the Saudi regulator, which permits the pledge of future assets and rights and establishes a unified commercial pledges registry to enhance transparency and determine creditors’ priorities. The research concludes that the legal framework governing pledge provides an effective balance between the creditor’s interest in obtaining reliable security and the debtor’s interest in utilizing property without transferring ownership. It also contributes to promoting credit, investment, and economic stability. The study recommends increasing legal awareness of pledge rules, simplifying registration and enforcement procedures, and continuing to update legislation to meet evolving economic and technological developments.